Zinc deficiency responses: bridging the gap between Arabidopsis and dicotyledonous crops. (17th November 2021) - Thiébaut, Noémie; Hanikenne, Marc
Abstract: Zinc (Zn) deficiency is a widespread phenomenon in agricultural soils worldwide and has a major impact on crop yield and quality, and hence on human nutrition and health. Although dicotyledonous crops represent >30% of human plant-based nutrition, relatively few efforts have been dedicated to the investigation of Zn deficiency response mechanisms in dicotyledonous, in contrast to monocotyledonous crops, such as rice or barley. Here, we describe the Zn requirement and impact of Zn deficiency in several economically important dicotyledonous crops, Phaseolus vulgaris, Glycine max, Brassica oleracea, and Solanum lycopersicum . We briefly review our current knowledge of the Zn deficiency response in Arabidopsis and outline how this knowledge is translated in dicotyledonous crops. We highlight commonalities and differences between dicotyledonous species (and with monocotyledonous species) regarding the function and regulation of Zn transporters and chelators, as well as the Zn-sensing mechanisms and the role of hormones in the Zn deficiency response. Moreover, we show how the Zn homeostatic network intimately interacts with other nutrients, such as iron or phosphate. Finally, we outline how variation in Zn deficiency tolerance and Zn use efficiency among cultivars of dicotyledonous species can be leveraged for the design of Zn biofortification strategies. Abstract : Zinc deficiency represents a major agronomic and health issue. Translating the massive knowledge acquired in Arabidopsis about zinc deficiency response mechanisms for biofortification of dicotyledonous crops is therefore paramount.